Inquiry into Digital Peer-to-Peer Platforms - Silva, Rosario; Gerwe, Oskana (Edward Elgard, 2023)
Peer-to-peer (P2P) platform businesses are an increasingly prevalent form of exchange that are becoming more diverse as they span across different industries. For the research on P2P platforms to move forward, it is important to have a clear view of what we understand under P2P platforms and how we can systematically conceptualize their heterogeneous universe. This conceptual paper has three objectives. First, it provides a definition of P2P platforms. Second, it develops a systematic classification of P2P platform businesses based on three salient dimensions: 1) asset that underlies the transaction (physical, human, digital asset or money); 2) mode of transaction (only online or online plus offline); and 3) monetary compensation (present or absent). Third, it maps the landscape of digital strategies that P2P platforms can use in order to attract, match and retain peer-providers and consumers.
Keywords: Peer-to-peer; Digital platform; Digital strategy; 53 Ciencias Económicas; ODS 9 - Industria, innovación e infraestructura